Dukungan Sosial dan Kecemasan sebagai Prediktor School Well-Being pada Siswa Pedalaman - Fakhri Yacob (Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to simultaneously examine social support and anxiety variables as predictors of well-being in Islamic senior high school students in remote areas, particularly students at MAN 2 Aceh Besar, who have different socio-economic characteristics, limited access to education, and high dependence on family, teacher, and peer support. This study found that the residual data were normally distributed (Asymp. Sig. = 0.712 > 0.05), so the regression model met the normality assumption and was suitable for hypothesis testing (normality test). The results of the regression analysis reported that social support had no significant effect on students' school well-being (β = 0.103; p = 0.416), although it had a positive relationship direction. Similarly, anxiety had no significant effect on school well-being (β = -0.063; p = 0.618), although it showed a negative relationship direction in accordance with the theory. These findings indicate that in students in remote or outer-city areas, school well-being is not directly determined by social support or anxiety. Student well-being at school is likely influenced by other factors, such as the quality of relationships with teachers, school climate, family support, resilience, learning engagement, and the local educational environment. Therefore, further research is needed to examine these variables to gain a more comprehensive understanding of the factors influencing students' school well-being in rural areas.